2005
DOI: 10.1007/s10494-005-4872-1
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Mixing Fields for Transported Scalar PDF Simulations of a Piloted Jet Diffusion Flame (‘Delft Flame III’)

Abstract: Abstract. Numerical simulation results are presented for 'Delft Flame III', a piloted jet diffusion flame with strong turbulence-chemistry interaction. While pilot flames emerge from 12 separate holes in the experiments, the simulations are performed on a rectangular grid, under the assumption of axisymmetry. In the first part of the paper, flow and mixing field results are presented with a non-linear first order k-ε model, with the transport equation for ε based on a modeled enstrophy transport equation, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 24 publications
(80 reference statements)
1
31
0
2
Order By: Relevance
“…5). This is in agreement with the known fact that the RKE performs well compared to SKE in round jet calculations not only for non-reacting turbulent flows [26], but also for reacting turbulent flow calculations [38,39].…”
Section: Prediction Of Velocity Statisticssupporting
confidence: 89%
“…5). This is in agreement with the known fact that the RKE performs well compared to SKE in round jet calculations not only for non-reacting turbulent flows [26], but also for reacting turbulent flow calculations [38,39].…”
Section: Prediction Of Velocity Statisticssupporting
confidence: 89%
“…The Delft Flame III is also a target in the TNF workshop series (http://www.sandia.gov/TNF). Several attempts have been conducted to model this flame using RANS formulations and various combustion models, including the transported PDF method with reduced and detailed chemistry [14,15,18,20]. Nooren et al [18] and Merci et al [15] have shown that transported PDF results are strongly dependent on the micro-mixing model used, especially in the case of the temperature PDFs, while Merci et al [15] reported that it was not possible to predict accurately both the RMS of the mixture fraction and the amount of local extinction.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its moderate Reynolds number, the Delft Flame has strong extinction and significant finite rate chemistry effects. It has only been investigated before by Merci et al [22,23] using RANS-PDF and by Ayache and Mastorakos [2] using a LES-CMC method. The flame is composed of a central fuel jet, surrounded by two concentric coflows of air.…”
Section: Experimental and Numerical Set-upmentioning
confidence: 99%
“…The main fuel jet is separated from the primary air stream by a rim of outer diameter 15 mm. The pilot flames are located on this rim and consist of 0.5 mm diameter holes located on a circle of 7 mm diameter in order to prevent flame lift-off [22]. The fuel used was commercially available Dutch natural gas (see composition in Table 1) with an adiabatic temperature T ad = 2216 K and a stoichiometric mixture fraction f st = 0.071 [28].…”
Section: Experimental and Numerical Set-upmentioning
confidence: 99%
See 1 more Smart Citation